2019
DOI: 10.1097/jhq.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in Pressure Injury Reporting: Creating Actionable Data for Improvement

Abstract: This department column highlights translation of research into health care quality practice. Achieving the highest quality of health care requires attention to developing and sustaining process efficiencies, and a thorough understanding of data and reporting. Mitigating or eliminating harm from pressure injuries may be more quickly achieved when accurate and consistent data are available for creating actionable interventions. The three aims of this project were to (1) confirm internally reported hospital acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…The HAPI analytical tool was built by an improvement team within the hospital to collect staged pressure injury attribution assigned by the Wound, Ostomy, and Continence (WOC) Team. 25 These HAPI data are considered the most accurate attribution of staging and are stored within the HAPI analytical tool managed by the hospital finance department. These data are identified by the date of attribution in the month when the injury is acquired and connected to the ICD-10 data for the month of discharge.…”
Section: Methodsmentioning
confidence: 99%
“…The HAPI analytical tool was built by an improvement team within the hospital to collect staged pressure injury attribution assigned by the Wound, Ostomy, and Continence (WOC) Team. 25 These HAPI data are considered the most accurate attribution of staging and are stored within the HAPI analytical tool managed by the hospital finance department. These data are identified by the date of attribution in the month when the injury is acquired and connected to the ICD-10 data for the month of discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Longer lengths of stay in the ICU and AIR may contribute to delay of acute care hospitals to discharge their patients and increased healthcare costs. For example, in 2019, Padula et al estimated that US hospitalacquired pressure injuries cost $10,708 per patient, and the U.S. had a national average of 2.5 million reported cases, potential costing $26.8 billion annually (33). The COVID-19 pandemic was an unprecedented challenge to the healthcare system as a whole in terms of resource and staff availability (36).…”
Section: Resultsmentioning
confidence: 99%
“…After noting a steady increase of pressure injuries during the first surge (March to May 2020), Polancich et al observed that prone placement was a significant risk factor for pressure injury development. Thus, they were able to implement interventional strategies, such as placing silicon adhesive dressings on pressure points on the prone patients ( 34 , 35 ). One such set of recommendations adapted for the care of COVID-19 patients in the acute care setting is summarized in Tables 6 , 7 , so that similar pandemic surges in the future will have decreased pressure injury incidence ( 36 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Administrative, demographic, and HAPI data were collated into an Excel spreadsheet from our hospital billing system and our internal HAPI analytic tool. 17 , 18 Patient demographic data were collected via a data steward using patient identifiers but were de-identified prior to analysis and provision to the study principal investigator.…”
Section: Methodsmentioning
confidence: 99%